Untargeted Tumor Metabolomics with Liquid Chromatography—Surface-Enhanced Raman Spectroscopy - Xiao, Lifu (Angew Chem Int Ed Engl, 2020)
Metabolomics is a powerful systems biology approach that monitors changes in biomolecule concentrations to diagnose and monitor health and disease. The leading metabolomics technologies, such as NMR and mass spectrometry (MS), currently access only a small portion of the metabolome, suggesting that new technologies with orthogonal and chemically specific capabilities can provide increased metabolome coverage and further advance the diagnostic power of metabolomics. Here we report a novel approach using the high sensitivity and chemical specificity of surface enhanced Raman scattering (SERS) for online detection of metabolites from tumor lysates following liquid chromatography (LC). Our results demonstrate that this LC-SERS approach has metabolite detection capabilities comparable to the state-of-art LC-MS but suggest a selectivity for the detection of a different subset of metabolites. Analysis of replicate LC-SERS experiments exhibit reproducible metabolite patterns that we convert into barcodes, which can differentiate different tumor models. Our work demonstrates the potential of LC-SERS technology for metabolomics-based diagnosis and treatment of cancer.